Readiness Analysis of Electronic Medical Record Implementation at Raja Ampat District Hospital Using DOQ-IT - Ani Dwi Andriyani; Wahyu Wijaya Widiyanto (Saintika Medika : Jurnal Ilmu Kesehatan dan Kedokteran Keluarga, 2025)
This study aims to assess the readiness of RSUD Kabupaten Raja Ampat for Electronic Medical Records (EMR) implementation using the DOQ-IT framework. The research focuses on four domains: Human Resources, Organizational Culture, Governance & Leadership, and Technology Infrastructure. A cross-sectional survey was conducted involving 150 respondents from various hospital departments. The findings indicate varying levels of readiness across domains, with the highest readiness observed in Governance & Leadership (76%), followed by Organizational Culture (70%), Human Resources (64%), and Technology Infrastructure (58%). Critical challenges include inadequate training, poor communication, and outdated infrastructure. Governance & Leadership demonstrated the strongest readiness due to management support, while Technology Infrastructure showed the lowest readiness due to network issues and hardware limitations. This study concludes that RSUD Kabupaten Raja Ampat is partially ready for EMR implementation. Effective strategies to address identified barriers include enhancing training programs, improving communication practices, and investing in updated infrastructure to achieve full readiness.